SISTEM PENDATAAN BARANG BERBASIS WEB (STUDI KASUS: PT. Perdana Cargo Solutions) - Gunawan Adhy Santoso; Bobby Ray Harianja; Elisa Damayanti (Shofanah Media Berkah, 2023)
Manual goods recording processes in the company's warehouse are still often carried out, resulting in several problems such as delays in the process of outgoing and incoming goods, physical data damage of goods, and accumulation of physical data documents in the warehouse. The development of information technology provides convenience in managing company data including goods data. One solution to overcome the above problems is to build a web-based goods recording system. This system can accurately, quickly and neatly record goods data. In addition, this system can also accelerate the process of outgoing and incoming goods and reduce damage and accumulation of data. A web-based goods recording system is important to achieve ease of data access and business process automation. This study aims to design a web-based goods recording system to create a goods system that can overcome manual problems and help company's business processes. This system is expected to improve the effectiveness and efficiency of managing company's goods data. PT. Perdana Cargo Solutions is a cargo shipping and logistics service company. The company is engaged in packing, shipping, shipping and storage of containers and shipping goods. Along with the development of business activities at PT. Perdana Cargo Solutions, the number of shipping goods also increased. The process of recording goods in the company's warehouse is currently still done manually, so there are several problems found, namely delays in the process of packing and shipping goods, goods data errors due to duplication of recording, and accumulation of physical documents of goods data. These issues make goods data management in the company become ineffective, both in terms of time and cost. Therefore, PT. Perdana Cargo Solutions requires a goods recording system that can improve the performance of managing goods data to support the company's business growth. One of the solutions is to build a web-based goods recording system. The webbased goods recording system is expected to accurately, integratively and timely record shipping goods data. In addition, this system also facilitates the process of packing and shipping goods and reduces delays due to data retrieval and duplication of records. With the implementation of this system, it is hoped that the performance of managing company's goods data can increase significantly along with the growth in business volume. The development of the web-based goods recording system aims to create an integrated, reliable goods management system and can support the scalability of PT. Perdana Cargo Solutions' business in the future.